2022
DOI: 10.31616/asj.2021.0140
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dural Tears in Open versus Minimally Invasive Spine Surgery: A Single-Center Prospective Study

Abstract: Study Design: A prospective comparative study.Purpose: To compare the incidence of unintended durotomy and return to work after open surgery versus minimally invasive spine surgery (MIS) for degenerative lumbar pathologies.Overview of Literature: The incidence of accidental durotomy varies between 0.3% and 35%. Most of these are from open surgeries, and only a handful of studies have involved the MIS approach. No single-center studies have compared open surgery with MIS, especially in the context of early retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Concerning surgical approaches, the literature comparing the various approaches to surgery with regard to IDT incidence is scarce [ 18 ]. The risk of IDT is often only mentioned in relation to open or minimally invasive surgery in the majority of studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning surgical approaches, the literature comparing the various approaches to surgery with regard to IDT incidence is scarce [ 18 ]. The risk of IDT is often only mentioned in relation to open or minimally invasive surgery in the majority of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we only detected IDT in patients who had open surgery. In a prospective comparative study with 420 patients, Sharma et al found a higher rate of IDT in patients who underwent an open approach compared to a minimally invasive approach (15.9% vs. 6.4%, respectively) [ 18 ]. In a minimally invasive approach, minimal tissue retraction is required; the surgeon can avoid midline scar tissue and fibrosis in previously operated patients; and a small amount of ligamentum flavum or lamina is removed to access the disc during discectomy, resulting in a lower chance of IDT.…”
Section: Discussionmentioning
confidence: 99%
“…It has clinical and radiological outcomes comparable to open spine surgery, can reduce approach-related harm (a drawback of open surgery), and preserves normal anatomy. Thus, postoperative recovery and return to regular life is quick [ 5 , 6 ]. The benefits of MISS include less bleeding during the procedure, quicker recovery period, and fewer postoperative complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it reduces soft-tissue dissection and maintains structural integrity of paraspinal musculature. 6…”
Section: Introductionmentioning
confidence: 99%
“…Also, it reduces soft-tissue dissection and maintains structural integrity of paraspinal musculature. 6 Intramuscular pressure has been seen to increase substantially in conventional open posterior spine surgery with use of self retaining retractors. Up to 36.80% of multifidus muscle (MFM) atrophy was seen in patients undergoing conventional open TLIF (CO-TLIF).…”
Section: Introductionmentioning
confidence: 99%